Architecture of the 90S pre-ribosome: a structural view on the birth of the eukaryotic ribosome - Kornprobst, Markus; Turk, Martin; Kellner, Nikola; Cheng, Jingdong; Flemming, Dirk; Koš-Braun, Isabelle C.; Koš, Martin; Thoms, Matthias; Berninghausen, Otto; Beckmann, Roland; Hurt, Ed (Cell, 2016)
The 90S pre-ribosome is an early biogenesis intermediate formed during co-transcriptional ribosome formation, composed of ∼70 assembly factors and several small nucleolar RNAs (snoRNAs) that associate with nascent pre-rRNA. We report the cryo-EM structure of the Chaetomium thermophilum 90S pre-ribosome, revealing how a network of biogenesis factors including 19 β-propellers and large α-solenoid proteins engulfs the pre-rRNA. Within the 90S pre-ribosome, we identify the UTP-A, UTP-B, Mpp10-Imp3-Imp4, Bms1-Rcl1, and U3 snoRNP modules, which are organized around 5′-ETS and partially folded 18S rRNA. The U3 snoRNP is strategically positioned at the center of the 90S particle to perform its multiple tasks during pre-rRNA folding and processing. The architecture of the elusive 90S pre-ribosome gives unprecedented structural insight into the early steps of pre-rRNA maturation. Nascent rRNA that is co-transcriptionally folded and given a particular shape by encapsulation within a dedicated mold-like structure is reminiscent of how polypeptides use chaperone chambers for their protein folding.